Beyond Kyoto: CO2 permit prices and the markets for fossil fuels - Lars Lindholt (Statistics Norway, Research Department, 1999)
This paper analyses the markets for fossil fuels given that the limits that the Kyoto Protocol sets on CO2 emissions from Annex B countries extend beyond 2008-2012. To our knowledge we are the first to apply a forward-looking model with endogenous prices for fossil fuels in analysis of specific CO2 emission targets, under different assumptions concerning OPEC behaviour. We calculate both the time-path of the international permit prices needed for the Kyoto targets as well as the implications through reduced demand and lower producer prices for fossil fuels. Irrespective of the assumption concerning OPEC behaviour, the permit price has to rise for the first 30 to 40 years in order to fulfil the Kyoto targets in Annex B. The permit price can be reduced substantially, dependent on when a backstop technology starts to replace oil. The Kyoto targets will result in a loss of petroleum wealth for oil and gas producers by 15 to 20 % as long as OPEC acts as a cartel. If the developing countries are included in the Protocol, OPEC will lose much more of their wealth. The competitive fringe has far more to lose if OPEC breaks down in the absence of these emission targets, than the implementation of the targets with OPEC as a cartel.
Keywords: H23; Q30; Q40; 330; The Kyoto Protocol; International CO2 permits; Exhaustible Resources; Petroleum wealth.